2013
DOI: 10.3402/polar.v32i0.18521
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temperature and fertilization on the structure of total versus active bacterial communities from sub-Antarctic seawater exposed to crude oil and diesel fuel

Abstract: François Ghiglione (2013) Effects of temperature and fertilization on the structure of total versus active bacterial communities from sub-Antarctic seawater exposed to crude oil and diesel fuel, Polar Research, 32:1, 18521,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 50 publications
1
5
0
Order By: Relevance
“…The relatively high background of hydrocarbon degrader microorganisms present in the sediments could suggest contamination at the collection site by accidental marine fuel contamination from the elevated naval traffic in the region, or runoff from fuel contaminated land. In the sediments, indigenous (naturally occurring) microbial community is increasing in numbers and activity when re-exposed to subsequent contamination events (Rodrıguez-Blanco et al, 2013).…”
Section: Increases In Respiration Rates and Hydrocarbon Degrading Micmentioning
confidence: 99%
“…The relatively high background of hydrocarbon degrader microorganisms present in the sediments could suggest contamination at the collection site by accidental marine fuel contamination from the elevated naval traffic in the region, or runoff from fuel contaminated land. In the sediments, indigenous (naturally occurring) microbial community is increasing in numbers and activity when re-exposed to subsequent contamination events (Rodrıguez-Blanco et al, 2013).…”
Section: Increases In Respiration Rates and Hydrocarbon Degrading Micmentioning
confidence: 99%
“…To avoid this issue, analyses based on RNA are required as well. Studies that aim to analyze bacterial activity by using 16S rRNA transcripts are well established for marine environments ( Wemheuer et al, 2012 , 2014 ; Rodríguez-Blanco et al, 2013 ; Zhang et al, 2014 ; Stibal et al, 2015 ). In soil and other terrestrial environments, however, only a limited number of RNA-based studies are available, which address the effects on land use conversion and showed that entire community analysis alone can lead to false conclusions regarding community activity ( Foesel et al, 2014 ; Herzog et al, 2015 ; Mueller et al, 2016 ; Ragot et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…The first is based on a cultivationbased approach that has been successfully employed to estimate the number of hydrocarbon-degrading bacteria in situ, as well as in laboratory conditions (Delille et al 2009;Johnsen and Henriksen 2009;Rodríguez-Blanco et al 2013). The second is a more recent molecular technique that quantifies the number of copies of genes responsible for the metabolism of pollutants, such as PAHs (Cebron et al 2008).…”
Section: Introductionmentioning
confidence: 99%